Designing a respectful maternity care guideline: a multiphase study - Khadije Hajizadeh; Maryam Vaezi; Shahla Meedya; Sakineh Mohammad Alizadeh Charandabi; Mojgan Mirghafourvand (BMC, 2022)
Plain language summary Disrespect and abuse in the delivery room is associated with negative experience of delivery and poor maternal care quality index. Also, disrespect and abuse is the main barrier to achieving maternal health outcomes. In spite of the considerable achievements in maternal and child health, there is still a large number of maternal and neonatal mortality worldwide. It seems that disrespect and abuse is a key potential obstacle hindering access to delivery facilities and skilled care providers. To achieve the sustainable development 2030 goals developed by the World Health Organization (WHO) (Goal 3.1: Ensure health lives and promote well-being for all at all ages: reduce the global maternal mortality ratio to less than 70 per 100,1000 live birth), stakeholders and relevant institutions should consider respectful pregnancy and delivery care services as a key solution to reducing maternal mortality. Nevertheless, there is no comprehensive guideline with regards to respectful maternity care in the WHO or provided by other countries. In this multiphase mixed-methods study, recommendations were made for respectful maternity care promotion through the data obtained from Phase I (i.e., the quantitative section with a cross-sectional design), Phase II (i.e., the qualitative section with a content analysis method), and Phase III (i.e., focus group discussions with birth attendants as well as opinions of the specialized panel through the Delphi technique). The composed recommendations were then analyzed and finalized by relevant specialists in terms of execution capacity, approvability, and cost-effectiveness within the current context of Iran. The results of this multiphase study led to 80 recommendations for RMC promotion. The recommendations were classified as eight areas called recommendations for the pregnancy period, recommendations for the labor period and delivery, recommendations for the neonatal period, occupational recommendations, supervision recommendations, national policy recommendations, recommendations for training students and staff, and general public recommendations.